Simulation of antihydrogen deexcitation in neutral atom traps for improved trapping and cooling. (16th February 2022) - Malbrunot, C; Wolz, T; Nowak, L; Comparat, D
Abstract: We present results of simulations highlighting the performance of a cooling mechanism in a magnetic trap tailored for excited Rydberg atoms (or molecules) with high magnetic moment. Unlike previous work, the cooling is achieved through fast stimulated decay of inter-manifold transitions which optimizes the scheme. This mechanism is relevant to experiments with trapped antihydrogen atoms for which the trapping fraction is currently low. We find several-fold enhancements of the number of atoms trapped in the configurations probed.